Effectiveness of a single emotional freedom techniques session on facilitating forgiveness and mental health: a randomized clinical trial - Peta Stapleton; Kyra Le Sech; Loren L. Toussaint; Hui Kuang Hsieh (Cogent Psychology)
Interpersonal transgressions can cause emotional distress and harm victims’ mental and physical health. This pre-registered clinical trial investigated the effectiveness of Emotional Freedom Techniques (EFT) in promoting forgiveness and mental health. A sample of 98 adults (91% female, aged 28–72) from Australia and the U.S. self-selected and were randomly allocated to an online EFT intervention or control task. Pre- and post-intervention measures assessed forgiveness, empathy, rumination, mood, and anxiety. Results revealed moderate improvements in most outcomes for the EFT group, suggesting its potential role in fostering forgiveness and psychological recovery. Findings suggest EFT may aid emotional reintegration, reduce stress, and enhance mental wellbeing after interpersonal offenses.